Культура фахового мовлення - Алєксєєв, М. М. (ХНУРЕ, 2021)
The culture of professional speech presupposes observance of linguistic norms of pronunciation, stress, construction of utterances, accuracy, clarity, logic, richness and appropriateness of speech, as well as observance of the rules of speech etiquette. Using information from the history of the Ukrainian literary language, grammar, lexicology, word formation, stylistics, speech culture develops scientific criteria for assessing language facts, identifies trends in the language system, conducts targeted language policy, promotes the implementation of norms in language practice